Primary Pulmonary Leiomyosarcoma in a Forty-Year-Old Woman - Ekin Ozluk; Eric X. Wei; James Cotelingam; Rodney E. Shackelford (Case Reports in Oncology, 2021)
Primary pulmonary leiomyosarcomas (PPLs) are rare aggressive malignancies originating from the smooth muscle cells of the pulmonary interstitium, bronchial tree, or blood vessels. Accounting for <0.5% of lung tumors, PPLs are often initially undetected or misdiagnosed as pulmonary emboli, cardiac neoplasms, or as other more common lung cancer subtypes. Due to their aggressive and often lethal clinical profile, the diagnostic delay of PPL can significantly affect patient outcomes and must be avoided. Here we describe a case of PPL in a 40-year-old woman.